2009
DOI: 10.1063/1.3246791
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relation between stress and surface morphology in sputtered films: Atomistic simulations and experiments

Abstract: Articles you may be interested inSuccessful fabrication of high K u columnar CoPt-SiO2 granular film sputtered under high substrate temperature J. Appl. Phys. 115, 17B752 (2014); 10.1063/1.4869164Unstable kinetic roughening during the island coalescence stage of sputtered tantalum films Interdependence between stress, preferred orientation, and surface morphology of nanocrystalline TiN thin films deposited by dual ion beam sputtering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
4
7
0
Order By: Relevance
“…5 In addition, for large deposition angles our results for the thin-film porosity were found to be in excellent agreement with recent experimental values. 9 In this case for both random and fixed φ we have also found that while the strain is initially compressive, it becomes tensile after the onset of columnar growth for large deposition angles, in good qualitative agreement with the behavior obtained previously by Zepeda-Ruiz et al 9 in sputter-deposition experiments on Be growth with and without substrate bias.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5 In addition, for large deposition angles our results for the thin-film porosity were found to be in excellent agreement with recent experimental values. 9 In this case for both random and fixed φ we have also found that while the strain is initially compressive, it becomes tensile after the onset of columnar growth for large deposition angles, in good qualitative agreement with the behavior obtained previously by Zepeda-Ruiz et al 9 in sputter-deposition experiments on Be growth with and without substrate bias.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we find that while the average strain is initially compressive for both random and fixed φ, it becomes tensile after the onset of columnar growth, in good qualitative agreement with recent experimental observations. 9 Our results also indicate that even on MD time-scales a variety of complex dynamical processes including coalescence, large-scale collective events, and budding play a key role in determining the evolution of the surface morphology and microstructure.…”
Section: Introductionsupporting
confidence: 52%
“…At higher growth rates, the films are susceptible to the formation of dendrites or other surface instabilities. Excessive surface roughness can lead to inaccuracy in estimated growth rate and porosity in the film (32). These effects can invalidate the mechanisms for stress generation that are included in the model.…”
Section: Comparison Of Experimental Results With Modelsmentioning
confidence: 99%
“…In this respect, we use the disappeared vacancy concentration as a surrogate for the stress evolution as previously done in Ref. 25. The number is normalized by the equilibrium GB vacancies in one substrate layer, and its average over five independent simulations is shown in Fig.…”
Section: Stress Control In Polycrystalline Thin Films-reduction In Admentioning
confidence: 99%